Effects of Biometrics on the Security of Enterprise Data and Information Assurance - Abong'o, Jaspher Asuga (JOOUST, 2015)
The increasing problem of user verification and identification has compelled institutions to adopt biometric based information security solutions, which rely on the uniqueness of the human physiological and behavioral characteristics that are mathematically measurable to provide stronger identification and verification. However, investigations into the effects of biometrics solutions on the security of enterprise data based on the concept of error have received little attention, creating a gap in academia on the use of biometrics as the most suitable choice to protect enterprise data. The research objectives that provide the framework for the study induce to investigating the accuracy of biometric identifiers, to compare biometrics with traditional authentication mechanisms such as passwords and tokens, and to investigate the technical issues, people issues, business issues, and operational issues and their effects on the security of enterprise data and information assurance. A combination of the information theory, the theory of reasoned action, and the technology acceptance model, the investigation used results from secondary sources for content analysis. The methodology consisted of collecting primary data from a sample size of 130 participants, which is above the 100 threshold size recommended for compliance with the NIST Patriot Act for investigating the feasibility of implementing biometrics in the information security architecture of an institution. Kisii and Nyamira level five hospitals were the areas of primary data collection with 118 respondents, 10 medical staff, and 2 IT professional, making the sample size of 130 from a target population of 650 people in 47 county hospitals. A statistical analysis of the results generated a Cronbach's Alpha of above 0.7 which showed a strong internal consistence, reliability and validity of the questionnaire constructs. Correlational descriptive statistics was used to generate SPSS tables for the questionnaire responses and 89.7% of the respondents confirmed they had been verified and identified using fingerprints. The results showed a strong correlation between the accuracy, technical, and business, privacy, and operational issues with information assurance, and it was established that any instance of breaching Confidentiality, Integrity, and Availability compromise the security of enterprise data. It was recommended that the intended beneficiaries of this research including the government, private and public businesses, and other corporate entities need to factor adjudication and formulate clear policies to intertwine biometrics with traditional authentication methods. However, further research on how to reduce biometric error rates could improve the reliability if biometrics for identification and verification.